2015
DOI: 10.1016/j.gca.2015.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of quartz overgrowth precipitation on the multiscale porosity of sandstone: A (U)SANS and imaging analysis

Abstract: We have performed a series of experiments to understand the effects of quartz overgrowths on nanometer to centimeter scale pore structures of sandstones. Blocks from two samples of St. Peter Sandstone with different initial porosities (5.8 and 18.3 %) were reacted from 3 days to 7.5 months at 100 and 200°C in aqueous solutions supersaturated with respect to quartz by reaction with amorphous silica. Porosity in the resultant samples was analyzed using small and ultrasmall angle neutron scattering and scanning e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 70 publications
2
43
0
Order By: Relevance
“…In discussing these three approaches, however, note that the regularization approach does not necessarily guarantee non-negative results for each bin. A similar multi-distribution pattern has been observed in sandstones (Anovitz et al 2013a(Anovitz et al , 2015a suggesting that modeling sandstones as a continuous fractal distribution is inappropriate.…”
Section: Reduction and Analysis Of Sas Datasupporting
confidence: 59%
See 4 more Smart Citations
“…In discussing these three approaches, however, note that the regularization approach does not necessarily guarantee non-negative results for each bin. A similar multi-distribution pattern has been observed in sandstones (Anovitz et al 2013a(Anovitz et al , 2015a suggesting that modeling sandstones as a continuous fractal distribution is inappropriate.…”
Section: Reduction and Analysis Of Sas Datasupporting
confidence: 59%
“…In the mid-Q range the data can be fi tted to a power-law slope. While we have shown that, in many cases, there are actually signifi cant details in this region (Anovitz et al 2013a(Anovitz et al , 2015a, to a fi rst approximation the log-log slope represents the fractal properties of the sample. Several scattering studies suggest that the length correlations of pore-grain interfaces can often be described by self-similar fractals with nonuniversal dimensions (2 < D < 3) (cf.…”
Section: Reduction and Analysis Of Sas Datamentioning
confidence: 80%
See 3 more Smart Citations